Women of piracy - Vandeberg, Brittany (Feminist criminology, 2023)
"Drawing from an interdisciplinary body of research and data, Women of Piracy employs a criminological lens to explore how women have been involved in, and impacted by, maritime piracy operations from the 16th century to present day piracy off the coast of Somalia. The book challenges and resists popular understandings of women as peripheral to the criminal enterprise of piracy by presenting and analyzing their roles and experiences as victims, perpetrators, and criminal justice actors, showing that women have been, and continue to be, central figures in maritime piracy. Unfolding in three parts, part one sets the context by providing readers with a history of the masculinization of the sea. Part two focuses on the gendered division of labor in piracy operations, discussing how and why the roles and responsibilities associated with this gendered labor have emerged, persisted, evolved, and/or ceased over time, as well as considering which roles and responsibilities appear to be context-specific and which seem to transgress geographical locations. Part three explores how women have (or have not) been brought to justice for their participation in crimes of piracy as well as the roles of women in efforts to combat piracy. The overarching objective is to ignite a broader discussion about the various cultural, social, historical, and economic forces that create opportunities for women to participate in maritime piracy and counter-piracy, why women continue to be invisible figures of piracy, and what implications this has for how we study, police, and bring pirates to justice. The first criminologically-grounded, global study exploring the continuity and evolution of women in maritime piracy, this book will be of great interest to students and scholars of criminology, gender, feminist studies, international relations, anthropology, history, and political geography. It will also be useful to maritime and law enforcement professionals"--